2022
DOI: 10.1038/s41598-022-09715-7
|View full text |Cite
|
Sign up to set email alerts
|

Feedlot diets containing different starch levels and additives change the cecal proteome involved in cattle’s energy metabolism and inflammatory response

Abstract: Diets for feedlot cattle must be a higher energy density, entailing high fermentable carbohydrate content. Feed additives are needed to reduce possible metabolic disorders. This study aimed to analyze the post-rumen effects of different levels of starch (25%, 35%, and 45%) and additives (monensin or a blend of essential oils and exogenous α-amylase) in diets for Nellore feedlot cattle. The cecum tissue proteome was analyzed via two-dimensional polyacrylamide gel electrophoresis (2D-PAGE) and then differentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Conversely, the increase in mPEPCK and G6Pase enzymes suggests an increase in carbohydrate synthesis and excretion, which could be a way for the fish to maintain glucose homeostasis as plant protein may not be as efficient at supplying energy as fishmeal [ 8 , 77 ]. The increases in FBPase and ENO1 may also suggest an increase in the synthesis of fructose-6-phosphate and pyruvate, which could provide more energy to fish [ 78 ]. The increased expression of ENO1, an enzyme involved in fermentation, observed in fish fed with plant protein-based diets may suggest that fermentation is more extensively used as a means of energy production due to the lower energy efficiency of plant protein compared to fishmeal [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the increase in mPEPCK and G6Pase enzymes suggests an increase in carbohydrate synthesis and excretion, which could be a way for the fish to maintain glucose homeostasis as plant protein may not be as efficient at supplying energy as fishmeal [ 8 , 77 ]. The increases in FBPase and ENO1 may also suggest an increase in the synthesis of fructose-6-phosphate and pyruvate, which could provide more energy to fish [ 78 ]. The increased expression of ENO1, an enzyme involved in fermentation, observed in fish fed with plant protein-based diets may suggest that fermentation is more extensively used as a means of energy production due to the lower energy efficiency of plant protein compared to fishmeal [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, acidification of the intestinal environment may lead to an increase in lesions in the cecal epithelium and a decrease in the number of goblet cells and enterocytes because the intestinal epithelium is more sensitive to pH changes than the rumen ( 64 ). However, in a companion study, Rocha et al ( 65 ) reported that cattle fed BEO plus amylase surprisingly did not have proteins related to inflammatory processes (leukocyte elastase inhibitors) in the cecal tissues, although cecal lesions increased in response to BEO. This could be because feed enzymes remain active in the intestine and can help digest nutrients that escape rumen fermentation, or they may have even had an anti-inflammatory effect, but they cannot control cecal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal epithelium was mechanically stimulated to secrete mucus, which they attributed to the effect of SCFAs on mucus thickening ( 69 ). The use of high-starch diets for cattle can lead to lesions and an inflammatory response in the cecum ( 65 ). Studies evaluating cecal morphometric parameters, cecal epithelial health, and the correlation of these parameters with animal performance are limited in the literature ( 44 , 70 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations